Changes in Resting-State Spontaneous Brain Activity in Patients With Allergic Rhinitis: A Pilot Neuroimaging Study - Gao, Ziang; Chen, Xixiang; Xiang, Rong; Zhang, Wei; Tan, Lu; Fan, Wenjun; Liu, Peiqiang; Lv, Hao; Xu, Yu (Frontiers in Neuroscience, 2021)
Background: Allergic rhinitis (AR) is an inflammatory disorder of the nose caused by IgE mediated immune response to allergens. Apart from typical symptom of sneezing, itching, rhinorrhea, and nasal congestion, behavioral complications were also reported to associated with the progression of AR, such as cognitive deficits, mood changes, memory decline, attention deficiency, poor school performance, anxiety and depression. Recent human studies suggested that alteration in brain function caused by allergen exposure may precipitate high levels of anxiety and emotional reactivity in asthma patients [10, 11] But till now, there is no direct evidence of the relationship between brain activity and allergic rhinitis. Methods: Resting-state functional magnetic resonance imaging (rs-fMRI) was used to excavate whether there remain functional changes of brain activity in AR patients. We measured the amplitude of low-frequency fluctuation (ALFF) and the z-conversion of ALFF (zALFF) in 20 patients with AR and 20 age- and sex-matched healthy controls (HCs) by the data of rs-fMRI. Results: Compared with the healthy controls, AR patients exhibited lower ALFF values in the precuneus (PCUN) and higher ALFF values in the anterior cingulate cortex (ACC). The ALFF values of these features were significantly correlated with the Visual Analogue Scale (VAS) scores, Rhino-conjunctivitis Quality of Life Questionnaire (RQLQ) scores, subscales of RQLQ, and total immunoglobulin E (IgE) partly. Conclusion: We found the changes in resting-state spontaneous brain activity in AR patients with hypoactivity in the precuneus (PCUN) and hyperactivity of the anterior cingulum cortex (ACC). The brain-related symptoms of AR might be another potential clinical intervention target for improving the life quality of AR patients. Further attention to brain activity is essential for the deeper understanding of AR.